1994
DOI: 10.1099/0022-1317-75-10-2635
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of primate sera to foamy virus Gag and Bet proteins

Abstract: In order to establish criteria for the serodiagnosis of foamy virus infections we investigated the extent to which sera from infected individuals of human and primate origin react with structural and non-structural virus proteins in immunoblot assays. Using lysates from infected cells as the source of virus antigen, antibodies were preferentially detected against the Gag proteins and the non-structural Bet protein. Both the Gag precursor molecules of 70 and 74K apparent M r and the cytoplasmic 60K M r Bet prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 60 publications
6
62
0
Order By: Relevance
“…However, to obtain this result, two nontemplated nucleotides, which were complementary to the terminal U5 dinucleotide, were added to the U3 substrate (Pahl & Flu$ gel, 1993). In addition, their introduction would destroy the bet reading frame overlapping the ppt-U3 border in all FVs Kupiec et al, 1991 ;Renne et al, 1992 ;Baunach et al, 1993 ;Hahn et al, 1994 ;Renshaw & Casey, 1994 b ;Herchenro$ der et al, 1994 ;Helps & Harbour, 1997 ;Winkler et al, 1997). Therefore, we suggest that the report of Pahl & Flu$ gel (1993) showed that FV IN is able to cleave some kind of elongated U3 end, which may arise through the generation of untidy ends during reverse transcription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to obtain this result, two nontemplated nucleotides, which were complementary to the terminal U5 dinucleotide, were added to the U3 substrate (Pahl & Flu$ gel, 1993). In addition, their introduction would destroy the bet reading frame overlapping the ppt-U3 border in all FVs Kupiec et al, 1991 ;Renne et al, 1992 ;Baunach et al, 1993 ;Hahn et al, 1994 ;Renshaw & Casey, 1994 b ;Herchenro$ der et al, 1994 ;Helps & Harbour, 1997 ;Winkler et al, 1997). Therefore, we suggest that the report of Pahl & Flu$ gel (1993) showed that FV IN is able to cleave some kind of elongated U3 end, which may arise through the generation of untidy ends during reverse transcription.…”
Section: Discussionmentioning
confidence: 99%
“…pHSRV2 or mutant plasmids were transfected into BHK\bel-1 cells, and 4 days later a cellular lysate was prepared in detergent buffer as described (Hahn et al, 1994). Following separation in SDS-8 % polyacrylamide gel and semi-dry blotting to nitrocellulose membranes (Schleicher & Schu$ ll), the viral proteins were allowed to react with Gag-specific, and following stripping of the blot with RNaseHspecific, rabbit antisera (Hahn et al, 1994 ;Ko$ gel et al, 1995) and stained using the ECL system (Amersham).…”
Section: Methodsmentioning
confidence: 99%
“…FV infections are persistent and infected animals show a sustained antibody response against Gag and Bet that is used for serological identification of infected hosts via ELISA and/or immunoblotting ( , [Hahn et al, 1994], [Heneine et al, 2003], [Khan and Kumar, 2006], [Saib, 2003] and [Williams and Khan, 2010]). Virus can commonly be isolated from infected cats, cattle and non-human primates ( , [Heneine et al, 2003], [Khan and Kumar, 2006], [Romen et al, 2007], [Saib, 2003] and [Williams and Khan, 2010]); however, no disease was associated with infections and thus, FVs are therefore considered apathogenic ( [Linial, 2000] and [Saib, 2003]).…”
Section: Introductionmentioning
confidence: 99%
“…22 It was detectable in HC-FAD-2-and HC-FAD-7-transduced cells (Figure 3a). In HC-FAD-8-transduced cells only the pr71 Gag precursor was stained, because p68 Gag is derived from protease-mediated cleavage of pr71 HC-FAD-7 is only able to perform the internal retrotransposition pathway of cells initially transduced by the hybrid vector.…”
Section: Introductionmentioning
confidence: 99%
“…22 Following centrifugation through the Qiashredder (Qiagen) to destroy high molecular weight (MW) nucleic acids, the proteins were separated in 7.5% polyacrylamide gels (SDS-PAGE) in a tricine buffer system. After blotting, the gels were reacted with mouse monoclonal antibodies (MABs) against PFV Gag and Pol proteins, 9,40,41 a rabbit antiserum against the PFV Env LP, 23 or with an MAB against human b-actin (Sigma).…”
Section: Protein Detectionmentioning
confidence: 99%